Evaluasi Penggunaan Obat Pada Pasien Geriatri Yang Memiliki Kemungkinan Interaksi Obat Berdasarkan Beers Criteria Di Rumah Sakit Umum Daerah Cilacap - Adityas, Hanung Puspita; Nurkholis, Fiqih; Hartono, Nurvadila Iqmalia (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: The increasing elderly population poses its own challenges, particularly in the field of health. The elderly tend to experience degenerative diseases and often have multiple chronic conditions. This can lead to the use of multiple medications (polypharmacy). Drug interactions occur when one medication affects the activity of another. These interactions can be pharmacokinetic or pharmacodynamic. The Beers Criteria is a tool used to detect Potentially Inappropriate Medications (PIMs) and identify drugs that may pose greater risks than benefits for elderly patients aged ≥ 65 years. Methods: This research uses descriptive method and is an observational study with a cross-sectional approach, measuring variables by collecting data through patient geriatric questionnaire. It aims to evaluate medication use in geriatric patients who may have drug interactions at Cilacap Regional General Hospital. Results: This research shows that female patients are more numerous, with 53 individuals (53.53%), while male patients amount to 46 individuals (46.46%). Patients in the age range of 60-74 years are 94 individuals (94.94%), and those in the age range of 75-90 years are 50 individuals (5.05%). Patients receiving <5 medication therapy are 57 individuals (57.57%), while those receiving >5 medications are 42 individuals (42.42%). The most commonly used medication among geriatric patients is candesartan, with 46 prescriptions (9.82%). The research results indicate that the medications falling under Potentially Inappropriate Medications (PIMs) according to the 2023 Beers criteria are mostly in category 1, totaling 81 medications (50.63%). Conclusion: The occurrence of Potentially Inappropriate Medications (PIMs) in geriatric patients at the outpatient department of Cilacap Regional General Hospital during the period of July-August 2024, based on the Beers Criteria 2023, shows that the largest percentage is attributed to glimepiride with 25 cases (17.606%). This indicates that prescribing PIMs to geriatric patients still involves potentially inappropriate drugs, necessitating attention from healthcare professionals to ensure safe and effective prescribing for this population.